STRATEGI PENGEMBANGAN EKOWISATA DALAM UPAYA MENDUKUNG PEMBERDAYAAN PETANI DI PERKOTAAN - Luh Putu Kirana Pratiwi (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
The scrape concept of world tourism towards an ecotourism model is due to the saturation of tourists to visit artificial tourism objects. The principle of ecotourism has an inseparable part by minimizing the negative impact of the surrounding environment through conservation efforts by maintaining the quality of the environment and local culture, as well as being able to empower the economy of the surrounding community. Subak in Bali have a role multifunctional and strategic role as a food producer and preservation of natural and cultural resources needed by the tourism industry. The involvement of local communities is the main key in tourism development, so the concept of empowerment arises as an effort to provide local communities to be free from voicelessness and powerlessness. In an effort to empower and preserve urban agriculture, the ecotourism development strategy model includes: (1) S-O strategy, to increasing agricultural productivity, tourist attractions, preserving the environment, and improving the economy of the community with tourism activities carried out. (2) S-T Strategy, to active participation of farmers in tourism management in Kertalangu Cultural Village, so as to increase income. (3) W-O strategy, to educate and counseling through Denpasar City government agencies to farmers related to tourism programs that are run and increasing varieties and agricultural productivity, so that marketing of agricultural products in tourism areas is more effective and profitable (4) W-T strategy, to establish cooperation with the government, other private parties to enhance tourism promotion and develop agricultural and cultural attractions in the future program sustainability.